2000
DOI: 10.1177/104649640003100305
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Entrainment in Engineering Design Teams

Abstract: In this article, the authors test the hypothesis that cycles of speaking and turn taking during group design discussions are entrained to rhythmic shifts in group-level modes of reasoning. Video recordings of six teams of engineering students performing realistic design tasks were coded for instances of figural and conceptual reasoning, rates of turn taking, and group participation. Exploratory spectral analysis pointed to rhythmic oscillations every 5 to 10 minutes between periods of predominantly figural or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Applied to team performance, a central tenet of social entrainment theory involves synchronization of member inputs to one another and to the "beat" of an external pacer (e.g., a consistent deadline), thus, establishingapace of coordinated behavior. The synchronization of interpersonal rhythms can involve regular patterns of verbal inputs such as orderly turn taking in group discussion and problem solving (Reid & Reed, 2000;Warner, 1992), or highly coordinated contributions of physical effort in musical groups and sports teams (McGrath, Kelly, & Machatka, 1984). If pacing cycles can be thought of as performance episodes that match the demands of the task environment (Marks et al, 2001), one implication is that more strongly entrained teams will be more efficient, as long as the task remains the same (Kelly, 1988).…”
Section: Teams Time and Entrainmentmentioning
confidence: 99%
“…Applied to team performance, a central tenet of social entrainment theory involves synchronization of member inputs to one another and to the "beat" of an external pacer (e.g., a consistent deadline), thus, establishingapace of coordinated behavior. The synchronization of interpersonal rhythms can involve regular patterns of verbal inputs such as orderly turn taking in group discussion and problem solving (Reid & Reed, 2000;Warner, 1992), or highly coordinated contributions of physical effort in musical groups and sports teams (McGrath, Kelly, & Machatka, 1984). If pacing cycles can be thought of as performance episodes that match the demands of the task environment (Marks et al, 2001), one implication is that more strongly entrained teams will be more efficient, as long as the task remains the same (Kelly, 1988).…”
Section: Teams Time and Entrainmentmentioning
confidence: 99%
“…We do not claim that team behaviours themselves are necessarily emergent. Even patterns of turn-taking in small group design discussions may not necessarily signal a peculiar group structure, but, instead, cognitive entrainment (Reid and Reed 2000). Rather, we do claim that social dynamics such as leadership, discord, shared understanding, and cohesion can be visualised by assuming that they arise emergently from the local interactions of the visual elements rather than by programming them 'hard-coded' into the visualisation.…”
mentioning
confidence: 94%
“…When we analyzed the observational data gathered from our engineering teams, we too found that rhythmic cycles of figural and conceptual design thinking emerged (Reid & Reed, 2000a). However, these cycles were also marked by distinctive patterns of group interaction-conceptual thinking appeared to predominate during highly interactive, sometimes noisy bursts of brief speaking turns involving nearly all members of the team, whilst figural thinking was confined to clusters of figural arguments dominated by individual designers, usually accompanied by sketching, and pointing or gesturing to sketch depictions.…”
Section: Conversational Disengagementmentioning
confidence: 96%
“…In the first of our studies (Reid & Reed, 2000a;Reid & Reed, 2000b), we focused on the time structure of these meetings, and in particular on the idea that design discussions progress through cycles of creative thinking in which individual designers develop potential design solutions whilst other group members listen attentively, and offer acknowledgment and support (Brereton, Cannon, Mabogunje, & Leifer, 1996). Rhythmic patterns underlying the thought processes of individual designers had already been observed by design researchers.…”
Section: Conversational Disengagementmentioning
confidence: 99%